Architectural Elements and Child Accidents in Elementary School Environments in the Lowokwaru District - Infaroyya Al Karimah Muhamad; Heru Sufianto (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2023)
Based on data from WHO and Riskedas, accidents involving children, including those that occur at schools, are known to have a high occurrence rate, with accidental injuries accounting for 21% of total child deaths. Among the age group of 5-14 years, which includes elementary school children, they contribute 9.7% to the overall figure. It is important to examine the architectural elements that often lead to accidents in elementary schools in the Lowokwaru District. This study focuses on the exterior areas within the elementary school environment. A qualitative method was employed, consisting of four stages: field observations, interviews with informants, problem identification, and recommendations. The findings indicate the need for improvements in dimensions of staircases that are not suitable for children, the use of slippery ceramic tiles in corridors, and uneven floor contours in the schoolyard. Recommendations include replacing the corridor floor with non-slip materials, using step nosings on the stairs, and adjusting the floor and ground contours to be more even.